A mathematical model and application for fire risk management in commercial complexes in South Africa (2020)
The successive event of fire mishaps in business buildings has been a significant issue. Accurately quantifying fire risks had been a complicated process due to its stochastic behaviour. Existing fire risk assessment applications are models dedicated to industrial fire hazards and wildfires. They are less suitable for fire risk analysis for the built environment. Also, most of these software require high rate subscriptions. More often than not, they require a highly-skilled programmer to use them. The development of a quantitative means for assessing the inclination of commercial complexes to a purported risk of “market fires‟ was done using the past fire accidents’ investigation reports. Some verified fire accident investigations were used to optimise the fire model; adopting the methodology highlights of the Qualitative Risk Assessment (QRA). A Visual Basic (VB) oriented computer programme for the model was developed to assess selected commercial buildings in Johannesburg city of South Africa. The model and the associated computer programme showed the accuracy of the developed fire risk model in forecasting fire hazards. The estimated fire risks correlated with the fire incident histories of the evaluated complexes, thus validating the model. The model application could be a useful tool for predicting fire accidents for stakeholders.